PURITY, RICHNESS, EXPRESSION OF SPEECH - Usmonova Zamira Jaxongirovna (Galaxy International Interdisciplinary Research Journal, 2021)
Linguistic elements that undermine the purity of speech, such as dialectics, barbarism (inappropriate, excessive use of foreign words), archaism.